2021
DOI: 10.1073/pnas.2111391118
|View full text |Cite
|
Sign up to set email alerts
|

USP15 antagonizes CRL4 CRBN -mediated ubiquitylation of glutamine synthetase and neosubstrates

Abstract: Targeted protein degradation by the ubiquitin–proteasome system represents a new strategy to destroy pathogenic proteins in human diseases, including cancer and neurodegenerative diseases. The immunomodulatory drugs (IMiDs) thalidomide, lenalidomide, and pomalidomide have revolutionized the treatment of patients with multiple myeloma (MM) and other hematologic malignancies, but almost all patients eventually develop resistance to IMiDs. CRBN, a substrate receptor of CUL4-RBX1-DDB1-CRBN (CRL4CRBN) E3 ubiquitin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 86 publications
3
24
0
Order By: Relevance
“…These results also suggest that patients with prior exposure to IMiD treatments may have limited response to CRBN-based PROTACs. In another study, it was found that upregulation of USP15, a deubiquitinating enzyme (DUB), can antagonize IMiDs and CRBN-based PROTAC-induced ubiquitination, thereby preventing degradation, suggesting DUB overexpression is another potential resistance mechanism to PROTACs ( Nguyen 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results also suggest that patients with prior exposure to IMiD treatments may have limited response to CRBN-based PROTACs. In another study, it was found that upregulation of USP15, a deubiquitinating enzyme (DUB), can antagonize IMiDs and CRBN-based PROTAC-induced ubiquitination, thereby preventing degradation, suggesting DUB overexpression is another potential resistance mechanism to PROTACs ( Nguyen 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot experiments then verified the expression of USP15. We found that the expression of USP15 in the two cell lines with the strongest metastatic and invasive abilities, MDA-MB-231 and SUM159; this result suggests that USP15 may affect breast cancer prognosis by altering the ability of tumor metastasis and invasion [ 55 ]. In addition, GO enrichment analysis and KEGG pathway analysis via the GESA database were performed on USP15.…”
Section: Discussionmentioning
confidence: 99%
“…Their specific involvement and impact on degrader efficacy has been limited, but an excellent example of USP15 counteracting CRBN molecular glue activity on particular neosubstrates has been shown. 71 The diversity of DUB:target specificities, and the inability to selectively inhibit DUBs makes them difficult to study in this context. In cases where degraders fail to efficiently ubiquitinate their targets, it is possible that the rate of deubiquitination by DUBs predominates (Fig.…”
Section: Mechanistic Steps Which Influence Overall Degradation Profilesmentioning
confidence: 99%